Sivelestat for septic patients with acute respiratory distress syndrome: a systematic review and meta-analysis of a deadly duo - Zheng, Wen-He; Hu, Yan-Ge; Yu, Da-Xing; Huang, Hui-Bin (Frontiers in Medicine, 2025)
BackgroundAcute respiratory distress syndrome (ARDS) is one of the most common organ dysfunctions in sepsis. The potential benefits of sivelestat, a selective inhibitor of neutrophil elastase, for patients with septic ARDS remain unclear. The current systematic review and meta-analysis aimed to evaluate the effectiveness of sivelestat in reducing mortality and improving other important outcomes in this patient population.MethodsWe searched PubMed, EMBASE, and Cochrane Library databases until May 30, 2025, for studies comparing sivelestat in septic patients with ARDS against controls. The primary outcome was mortality. We assessed study quality and conducted subgroup analyses, sensitivity analyses, regression analyses, and GRADE evaluations to explore potential heterogeneity.ResultsA total of 17 studies involving 5,062 patients met the inclusion criteria. Overall, sivelestat significantly reduced the risk of mortality compared to controls (odds ratio [OR] = 0.63; 95% confidence interval [CI], 0.48–0.84; I2 = 39%). Meta-regression showed that differences in baseline PaO2/FiO2 and risk of mortality significantly influence the effectiveness of sivelestat interventions, as shown in sequent subgroup analyses of patients with partial pressure of oxygen/fraction of inspiration oxygen (PaO2/FiO2) < 200 mmHg (OR = 0.61; 95% CI 0.51–0.73) and those with a mortality rate greater than 30% (OR = 0.48; 95% CI 0.37–0.60). A similar result was found when we pooled results from adjusted regression analyses (hazard ratio = 0.48; 95% CI 0.28–0.82). Additionally, sivelestat significantly improved PaO2/FiO2 on days 1, 3, 5, and 7 after treatment and was associated with a significant reduction in the duration of mechanical ventilation (standardized mean difference [SMD] = −0.58 days; 95% CI, −0.96 to −0.19), and length of ICU stay (SMD = −0.76 days; 95% CI, −1.09 to −0.43).ConclusionSivelestat significantly increased PaO2/FiO2 levels after treatment, leading to a improvement in mortality and other clinical outcomes. Further studies with well-designed protocols for administering sivelestat are needed to validate these findings.Systematic review registrationhttps://inplasy.com/wp-content/uploads/2025/06/INPLASY-Protocol-7969.pdf, identifier INPLASY202560111.